Facilitating the collaborative design of flexible learning materials: Investigating the synthesis of content and multimedia knowledge and expertise - Sinclair, Mark; Aldred, Scot; Smith, Richard (Australasian Journal of Educational Technology, 2002)
This paper discusses how teachers of English as a Second Language (TESOL) and educational multimedia experts collaborated in order to design a CD-ROM aimed at assisting international students to prepare for the International English Language Testing Service (IELTS) English Language Speaking test. The research focuses on the synthesis of content and multimedia knowledge and expertise. It shows how this synthesis occurred, and makes suggestions for how the collaboration necessary for such design work can be facilitated.